Asset Pricing Model Suitability: Evidence from USA, UK, and India - Rahman, Tareque (2018)
This study examines firms from USA, UK, and India and attempts to determine whether a standard or behavioral model is more suitable for the purpose of asset pricing. The standard model used is the Fama and French (1993) three factor model and the behavioral model is constructed based on the model presented in Shefrin and Statman (1995). All factors of the Fama-French model are found significant in UK and India, indicating that it is still effective in the modern world and size and value effect still persist. HML is found insignificant in USA, indicating that value effect may be disappearing in the US market. The intercepts are close to zero, suggesting that the models are well-defined. In all three markets, smaller firms are exposed to higher systematic risk than larger firms on average. In USA and India, value stocks carry more risk than growth stocks. This suggests that smaller and value stocks earn higher return because they carry higher risk. All variables of the behavioral model are also to a great extent found to be significant in USA and UK. This indicates that the behavioral model is also effective. This study also finds that investors seem to judge stocks of well-reputed companies as good stocks to invest in. The stock beta, which was found insignificant in previous studies, is found to be a significant explanator of company reputation. Realized returns estimated by the Fama-French model and expected returns estimated by the behavioral model are compared with one another to detect errors in investment decision-making process. Investors in USA demonstrate accurate and rational judgment, indicating that a standard asset pricing model is more suitable. Investors in UK and India display erroneous judgment and irrationality, making the behavioral model more appropriate. However, this particular behavioral model performs poorly in India, possibly as a result of poor reputation scores obtained from the reputation surveys of Fortune 500 India.